Discursos do conflito entre os diferentes agentes mediadores dos movimentos envolvidos no caso Eldorado do Carajás: novas tendências e práticas políticas - SILVA, Henry Willians Silva da (Universidade Federal do Pará, 2014)
The thesis was based to analyze the actions and speech of the various mediating agents of non-various government departments involved with the defense of causes and social movements struggling for land in the States of Pará. The grounds underpinning the analysis of speech analysis belong to the French line. The survey is a qualitative-descriptive kind. The interview questionnaire served as an instrument for the production of data. The results indicated that there were various speeches and performances focused upon the dispute for land rights, claims, justice and challenge to social order. Consequently, the social movements’ struggles and conflicts against the state policy in the Amazon Region have increased. There has been positive activist discussions over the struggle as a strategy to agrarian sustain over the relevance conflict in Pará, used as an outcome to its opponents. It also establishes the possibility of carrying out public policies in remote areas neglected by the government as well as the criminalizing of conflicts.